Long non‐coding RNA SNHG1 activates glycolysis to promote hepatocellular cancer progression through the miR‐326/PKM2 axis. (25th July 2022) - Wang, Yue; Yang, Fan; Peng, Qi; Mei, Ke; He, Haitao; Yang, Qing
Abstract: Background: Hepatocellular cancer (HCC) is a lethal malignancy with extremely poor prognosis. In the present study, we aimed to investigate the role and underlying mechanism of SNHG1 in HCC progression. Methods: Combined with bioinformatics and experimental validation, we explored the clinical significance of SNHG1 in HCC. A Cell Counting Kit‐8 assay, cell colony formation assay, and subcutaneous tumorigenesis experiments of nude mice were conducted to evaluate the pro‐proliferative capacity of SNHG1. Glucose consumption and lactate production were measured to explore the regulatory role of SNHG1 in glycolysis. Nuclear‐cytoplasmic separation, quantitative real‐time polymerase chain reaction and Western blot assays, chromatin immunoprecipitation, and luciferase reporter and RNA immunoprecipitation assays were performed to investigate the molecular mechanisms of SNHG1 in HCC. Results: SNHG1 expression was dramatically increased in HCC and positively correlated with poor prognosis. E2F1 bound to the SNHG1 promoter region to activate SNHG1 transcription. Furthermore, SNHG1 served as a molecular sponge for miR‐326 to sequester the interaction of miR‐326 and pyruvate kinase M2 (PKM2), facilitating the expression of PKM2. Activating PKM2 expression was revealed to be one of mechanisms of SNHG1 with respect to promoting glycolysis and the proliferation of HCC cells. Conclusions: E2F1‐activated SNHG1 modulates the miR‐326/PKM2 axis to facilitate glycolysis and the proliferation of HCC cells. Targeting SNHG1 could be a promising therapeutic option for HCC. Abstract : In hepatocellular cancer cells, elevated E2F1 activates SNHG1 transcription and thus upregulates SNHG1 expression. E2F1‐activated SNHG1 binds to miR‐326 and sequesters the interaction of miR‐326 and PKM2, resulting in upregulation of PKM2 expression, thus facilitating glycolysis and promoting the proliferation of hepatocellular cancer cells.